Fuzzy decision support system for english language teaching with corpus data - Meilin Huang (Egyptian Informatics Journal)
Corpus data from the past and novice observations are useful in improving the adeptness of English language teaching in high schools. Optimization methods support this adeptness through fine-tuning processes acquired from the corpus data. Hence, this article introduces a Progression-focused Teaching System (PTS) optimized by Fuzzy Decision (FD). This system focuses on identifying and providing solutions for lexical placement errors. Focusing on the progression of English teaching with high-quality outputs, lexical arrangement, and error reduction is pursued. The fuzzy decision system identifies a maximum precision output from the possible lexical placement in teaching vocabulary. In this decision process, the teaching efficiency towards the specific output is tuned through personalized training recommendations. The fuzzy output is used to benchmark the maximum precision output for further teaching references. Therefore, a consistent progression in teaching English vocabulary is attained by rectifying the errors in the previous corpus inputs.